Pemanfaatan Ekstrak Daun Mangga (Mangifera foetida L.) sebagai Penurun Asam Urat dalam Biji Melinjo - Dewangga, Pramudia Bagus; Larasati, Ulys; Salamah, Siti (CHEMICA: Jurnal Teknik Kimia, 2014)
Melinjo plants including the types of old plants. Uric acid is the final metabolisme result of purine, purine is one of the components of nucleic acids contained in the body of the cell nucleus. Gout disease to result from consume excessive of purine substances. This reaserch to reduce uric acid levels in seeds melinjo order melinjo seeds can be processed into refined products chips with low uric acid using blanching method from mango leaf extract.This research was making young mango leaf extract using distillate water as a solvent. Melinjo seeds that have been peeled after then process blanching is carried out using a preliminary heating at a temperature of less than 80-90 Â°C for 8 minute , using young mango leaf extract. Water immersion Melinjo is filtered, then analyzed in the Clinical Pathologyn Laboratory University of Gadjah Mada.This research was conducted with seed weight variable 10, 20, 30, 40, 50, 60 grams. Other variabels such as differences in the length of time 20,40,60,80,100,120 minutes. From the preliminary data showed that levels of uric acid in the melinjo seed is 222 mg / 100 g.The result of this research were the highest decrease in uric acid levels using variable melinjo seed weight 10 gr with immersion time of 30â is 17.86%. Using seed weight 10gr melinjo carried back to the old variable immersion study obtained results decreased levels of uric acid melinjo seed with most optimal immersion time is 100â with a decrease of 18.43989%.